Answer:
![a = -6, b = - 8](https://img.qammunity.org/2021/formulas/mathematics/high-school/7k9asfyttncal2ed9qlxen5bvvkal0wggd.png)
Remaining factor =
![x+4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wa8754nh7kxn1z7rzenclli1rrm9e4vu2h.png)
Explanation:
Given that:
Two polynomials:
and
![x^3 +3 x^2 +ax +b](https://img.qammunity.org/2021/formulas/mathematics/high-school/r7li99xtcucxjsxhrnacyanafmwhpdzpqy.png)
is a factor of
.
To find:
The values of
and
from the cubic equation and the remaining factor.
Solution:
Let us first of all, factorize
.
![x^(2) -2x+x-2=0\\\Rightarrow x(x-2)+1(x-2)=0\\\Rightarrow (x+1)(x-2)=0\\\Rightarrow x = -1, 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/3krueblugce00kx5uceboy3hg3izycgng0.png)
There are two factors of the given quadratic equation.
These two factors must also be factors of the cubic equation as well.
Putting
:
![2^3 +3 * 2^2 +a* 2 +b =0\\\Rightarrow 2a+b=-20 ..... (1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/r5nbqvk8rlcvxl1ysw42xhwbv3qfp36t3x.png)
Putting
:
![(-1)^3 +3 * (-1)^2 +a* (-1) +b =0\\\Rightarrow -a+b=-2 ..... (2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/lvyyx4l53dimsg23qr2tpgkscnj1pa6nfb.png)
Subtracting (2) from (1):
![3a = -18\\\Rightarrow a = -6](https://img.qammunity.org/2021/formulas/mathematics/high-school/7uw0f6mx94u00yeet7bna1dcvsnhucdi8r.png)
From equation (1):
![2* (-6) + b=-20\\\Rightarrow b = -8](https://img.qammunity.org/2021/formulas/mathematics/high-school/o3jrs0jmgi75otmy2brydbbhac06nk493y.png)
Putting the values of
and
in the cubic equation, we get:
![x^3 +3 x^2 -6x -8](https://img.qammunity.org/2021/formulas/mathematics/high-school/timm0h85j32lzbub1vm6ooke5iddp18o0e.png)
Dividing the cubic equation with quadratic, we get:
![(x^3 +3 x^2 -6x -8)/(x^(2) -x-2) = x+4](https://img.qammunity.org/2021/formulas/mathematics/high-school/5rlsec6hlnytam06xig9nl1e2stkqpzk9u.png)